PDCT-03. A PHASE II TRIAL OF POLY-ICLC IN THE MANAGEMENT OF RECURRENT OR PROGRESSIVE PEDIATRIC LOW GRADE GLIOMAS. RESULTS FOR THE NEUROFIBROMATOSIS 1 GROUP. (NCT01188096). (5th November 2018) - Aguilera, Dolly; MacDonald, Tobey; Castellino, Robert; Janss, Anna; Mazewski, Claire; Kadom, Nadja; Pu, Minya; Messer, Karen; Crawford, John; Connelly, Erin; Gray, Rachel; Salazar, Andres; et al.
Abstract: BACKGROUND: Polyinosinic-Polycytidylic acid stabilized with polylysine and carboxymethylcellulose (poly-ICLC) is a double stranded RNA that acts as a ligand for the Toll Receptor 3 (TLR3) and results in a broad host defense stimulation, including T-cell and natural killer cell activation and cytokine release (interferons alpha, beta, and gamma, interleukins, corticosteroids, and TNF). The goal of this trial is to determine the efficacy of this novel immunotherapy against refractory pediatric low-grade glioma (LGG). Here we present the results for the neurofibromatosis group. METHODS: Poly-ICLC 20mcg/kg/dose IM was self-administered twice a week at home for up to 24 cycles. Each cycle is 28 days. Endpoints include objective tumor response rate, progression-free survival (PFS), and rate of stabilization/improvement in visual examination in those with optic pathway glioma. RESULTS: Twenty three patients were enrolled, six with NF-1. Of NF1 patients (3 males, 3 females), five were evaluable, ages 1–16 years. Tumor location: 4 optic pathway, one thalamic, one cervico-medullary junction. 5/6 had received more than 2 prior regimens (range 1–7). Responses (PR+SD) were observed in 4/5 (80%), with 2 SD having a decrease in tumor size by 35% and 10%, one of whom had significant improvement on visual field testing, and 2 PR having decrease in tumor size by 50% and 55%. Only low grade toxicities were observed with poly-ICLC, including erythema and pain at site of injection, fever, myalgias, and ALT elevation. One intra-tumoral hemorrhage occurred with complete resolution with medical management alone. All patients are alive. CONCLUSION: Poly-ICLC is extremely well tolerated in the NF-1 group and the single agent response rate in this small NF1 cohort is encouraging. Expanded phase II testing of poly-ICLC in the NF-1 cohort is planned.